Variants in the ethylmalonyl‐CoA decarboxylase (ECHDC1) gene: a novel player in ethylmalonic aciduria?. Issue 5 (8th June 2021) - Fogh, Sarah; Dipace, Graziana; Bie, Anne; Veiga‐da‐Cunha, Maria; Hansen, Jakob; Kjeldsen, Margrethe; Mosegaard, Signe; Ribes, Antonia; Gregersen, Niels; Aagaard, Lars; Van Schaftingen, Emile; Olsen, Rikke K. J.
Abstract: Ethylmalonic acid (EMA) is a major and potentially cytotoxic metabolite associated with short‐chain acyl‐CoA dehydrogenase (SCAD) deficiency, a condition whose status as a disease is uncertain. Unexplained high EMA is observed in some individuals with complex neurological symptoms, who carry the SCAD gene ( ACADS ) variants, c.625G>A and c.511C>T. The variants have a high allele frequency in the general population, but are significantly overrepresented in individuals with elevated EMA. This has led to the idea that these variants need to be associated with variants in other genes to cause hyperexcretion of ethylmalonic acid and possibly a diseased state. Ethylmalonyl‐CoA decarboxylase (ECHDC1) has been described and characterized as an EMA metabolite repair enzyme, however, its clinical relevance has never been investigated. In this study, we sequenced the ECHDC1 gene ( ECHDC1 ) in 82 individuals, who were reported with unexplained high EMA levels due to the presence of the common ACADS variants only. Three individuals with ACADS c.625G>A variants were found to be heterozygous for ECHDC1 loss‐of‐function variants. Knockdown experiments of ECHDC1, in healthy human cells with different ACADS c.625G>A genotypes, showed that ECHDC1 haploinsufficiency and homozygosity for the ACADS c.625G>A variant had a synergistic effect on cellular EMA excretion. This study reports the first cases of ECHDC1 gene defects in humans and suggests that ECHDC1 may be involved in elevated EMA excretion in only a small group of individuals with the common ACADS variants. However, a direct link between ECHDC1 / ACADS deficiency, EMA and disease could not be proven.